Abdominal Adiposity Distribution Quantified by Ultrasound Imaging and Incident Hypertension in a General Population. Issue 5 (November 2016) - Seven, Ekim; Thuesen, Betina H.; Linneberg, Allan; Jeppesen, Jørgen L.
Abstract : Abdominal obesity is a major risk factor for hypertension. However, different distributions of abdominal adipose tissue may affect hypertension risk differently. The main purpose of this study was to explore the association of subcutaneous abdominal adipose tissue (SAT) and visceral adipose tissue (VAT) with incident hypertension in a population-based setting. We hypothesized that VAT, rather than SAT, would be associated with incident hypertension. VAT and SAT were determined by ultrasound imagining in 3363 randomly selected Danes (mean age 49 years, 56% women, mean body mass index 25.8 kg/m 2 ). We constructed multiple logistic regression models to compute standardized odds ratios with 95% confidence intervals per SD increase in SAT and VAT. Of the 2119 normotensive participants at baseline, 1432, with mean SAT of 2.8 cm and mean VAT of 5.7 cm, returned 5 years later for a follow-up examination and among them 203 had developed hypertension. In models including both VAT and SAT, the Framingham Hypertension Risk Score variables (age, sex, smoking status, family history of hypertension, and baseline blood pressure) and glycated hemoglobin, odds ratio (95% confidence interval) for incident hypertension for 1 SD increase in VAT and SAT was 1.27 (1.08–1.50, P =0.004) and 0.97 (0.81–1.15, P =0.70), respectively. Adjusting for body mass index instead of SAT attenuated the association between VAT and incident hypertension, but it was still significant (odds ratio, 1.22 [1.01–1.48, P =0.041] for each SD increase in VAT). In conclusion, ultrasound-determined VAT, but not SAT, was associated with incident hypertension in a random sample of Danish adults. Abstract : Supplemental Digital Content is available in the text.